2011
DOI: 10.4161/cbt.12.11.18366
|View full text |Cite
|
Sign up to set email alerts
|

New variants at 10q26 and 15q21 are associated with aggressive prostate cancer in a genome-wide association study from a prostate biopsy screening cohort

Abstract: ; Toronto ON Canada Purpose: To identify and examine polymorphisms of genes associated with aggressive and clinical significant forms of prostate cancer among a screening cohort.Experimental Design: We conducted a genome-wide association study among patients with aggressive forms of prostate cancer and biopsy-proven normal controls ascertained from a prostate cancer screening program. We then examined significant associations of specific polymorphisms among a prostate cancer screened cohort to examine their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 24 publications
2
30
1
Order By: Relevance
“…Our analysis suggests that rs10788160-A is associated with higher PSA levels, whilst rs10788160-G is associated with lower levels. A previous study reported a positive association between rs11199874-G and PrCa (25). This association could be driven by the large proportion (>50%) of high PSA (4-10 ng/ml) controls used rather than reflecting a true association because this high PSA enriched control sample is likely to have a higher proportion of individuals with the allele rs11199874-A; this could in turn account for the positive association of PrCa with rs11199874-G (the opposite allele to rs11199874-A).…”
Section: Discussionmentioning
confidence: 89%
“…Our analysis suggests that rs10788160-A is associated with higher PSA levels, whilst rs10788160-G is associated with lower levels. A previous study reported a positive association between rs11199874-G and PrCa (25). This association could be driven by the large proportion (>50%) of high PSA (4-10 ng/ml) controls used rather than reflecting a true association because this high PSA enriched control sample is likely to have a higher proportion of individuals with the allele rs11199874-A; this could in turn account for the positive association of PrCa with rs11199874-G (the opposite allele to rs11199874-A).…”
Section: Discussionmentioning
confidence: 89%
“…A meta-analysis aimed at determining whether genetic variants were associated with adverse pathology features reported that SNP rs11672691 showed associations with more aggressive tumors (Amin Al Olama et al 2013). Additionally, results from other GWAS and linkage analyses have reported risk loci associated with aggressive disease amongst familial cases (Casey et al 2006; Chang et al 2005; Gudmundsson et al 2008; Kirkland et al 2010; Liu et al 2011; Nam et al 2011; Nurminen et al 2011; Schaid et al 2006; Schaid et al 2007; Slager et al 2006; Stanford et al 2006; Witte et al 2000). In addition, Shui et al reported that 8 SNPs were associated with lethal PC (Shui et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis involves the division and migration of endothelial cells and leads to microvasculature formation (3,4). Based on the genome-wide association studies (GWAS), angiogenesis genetic variants or single nucleotide polymorphisms (SNPs) in or near IL-16 (rs4072111) and FGFR2 (rs11199874, rs10749408 and rs10788165) are significantly associated with PCa aggressiveness (5,6). In candidate gene studies, several angiogenesis SNPs are shown to be associated with PCa prognosis.…”
Section: Introductionmentioning
confidence: 99%